Hypothermia in Multiple Sclerosis: Beyond the Hypothalamus? A Case Report and Review of the Literature - Francesco Berti; Zeeshan Arif; Cris Constantinescu; Bruno Gran (Case Reports in Neurological Medicine)
Hypothermia is a rare and poorly understood complication of Multiple Sclerosis (MS). We report on a 66-year-old patient currently with Secondary Progressive MS (SP-MS) who developed unexplained hypothermia associated with multiple hospitalisations and we review the literature on this topic. In our case, magnetic resonance imaging (MRI) of the brain failed to highlight hypothalamic disease, but spinal MRI identified a number of spinal cord lesions. Given the incidence and clinical significance of spinal involvement in MS and the hypothermic disturbances observed in high Spinal Cord Injury (SCI), we hypothesise that upper spinal cord pathology, along with hypothalamic and brainstem dysfunctions, can contribute to hypothermia.